Geographic information systems - tool for evaluation of the hydro-energy performance of water supply systems - Santos, Aline Christian Pimentel Almeida; Pereira, José Almir Rodrigues; Rego, Augusto da Gama; Santos, Rogério da Silva (Acta Scientiarum. Technology, 2017)
The most relevant challenges in the water supply system (WSS) are high water losses and the waste of electric energy. This paper aimed to assess the capacity of the Geographic Information System (GIS) in the analysis of the hydro-energy performance of WSSs. The Stage 1 comprises the selection of data and the respective hydro-energy indexes are defined; cartographic data are defined in Stage 2 and a geo-referenced database is constructed in Stage 3. In the stage 4, the data of the Central Water Supply Zone administered by the Water Works Company of the state of Pará in Belém, Brazil were employed to assess its applicability, in which the sectors with the worst hydro-energy performance were identified, such as Sector 9, with the highest water loss rates (59.11%) and electric energy consumption per m3 of water produced (1.57 kwh m-Â³). The results shows that geo-referential assessment of the hydro-energy performance of WSSs provided accurate information for decision-taking related to the rational use of water and electricity in the systems. Â 